"Ghost imaging" in pericardial cavity: Disappeared "tumor‐like" masses in tuberculous pericarditis. Issue 1 (29th September 2022) - Chen, Tienan; Wang, Tingting; Yan, Yingqun; Qiao, Shuai; Xu, Xiaona; Che, Jingjin; Li, Guangping; Fu, Huaying
Abstract: A 66‐year‐old woman was admitted to our hospital due to chest distress and shortness of breath during 1 week. Transthoracic echocardiography (TTE) revealed massive pericardial effusion and multiple, irregular and high‐density echo "tumor‐like" masses on the heart, with the largest one on the apex. However, there were no masses found by computed tomography (CT) scan, except for increased lipids around the coronary artery. We performed emergency pericardiocentesis and drainage to relieve symptoms. The positron emission tomography/CT (PET/CT) also showed several ununiformly high accumulations in pericardial cavity. However, the high‐density echo "tumor‐like" masses cannot be seen by TTE after pericardiocentesis, and also cannot be detected when surgery. Pericardiotomy was performed due to severe pericardial adhesion. The diagnosis of tuberculosis (TB) was confirmed by pericardiotomy and pericardial biopsy. Abstract : We report a case of a 66‐year‐old woman with tuberculous pericarditis that showed multiple "tumor‐like" masses in pericardial cavity by transthoracic echocardiography (TTE), with a huge mass on the apex.